2018
DOI: 10.1038/s41467-018-04392-5
|View full text |Cite
|
Sign up to set email alerts
|

mTOR coordinates transcriptional programs and mitochondrial metabolism of activated Treg subsets to protect tissue homeostasis

Abstract: Regulatory T (Treg) cells derived from the thymus (tTreg) and periphery (pTreg) have central and distinct functions in immunosuppression, but mechanisms for the generation and activation of Treg subsets in vivo are unclear. Here, we show that mechanistic target of rapamycin (mTOR) unexpectedly supports the homeostasis and functional activation of tTreg and pTreg cells. mTOR signaling is crucial for programming activated Treg-cell function to protect immune tolerance and tissue homeostasis. Treg-specific deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
176
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(187 citation statements)
references
References 69 publications
(162 reference statements)
8
176
2
1
Order By: Relevance
“…Chapman et al. showed that mTOR signaling is necessary for Treg cell activation and tissue Treg homeostasis by means of a genetic Treg‐specific deletion of mTOR . In contrast, Battaglia et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chapman et al. showed that mTOR signaling is necessary for Treg cell activation and tissue Treg homeostasis by means of a genetic Treg‐specific deletion of mTOR . In contrast, Battaglia et al.…”
Section: Discussionmentioning
confidence: 99%
“…The role of mTOR signaling in immune tolerance and the possibility of targeting metabolic pathways in order to restore immune tolerance are matters of intensive current research. Chapman et al showed that mTOR signaling is necessary for Treg cell activation and tissue Treg homeostasis by means of a genetic Tregspecific deletion of mTOR [21]. In contrast, Battaglia et al showed that rapamycin selectively expands Tregs [22] and Delgoffe et al showed that mTOR deficient T cells differentiate toward Treg cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…106,107 Interestingly, phosphoproteomic analysis reveals that TCR-induced CAD phosphorylation is mTORC1-dependent, suggesting that mTORC1 also regulates pyrimidine synthesis in T cells. 101 mTORC1-dependent immune responses are also dictated by mitochondrial function, 101,115 which is induced in T cells downstream of mTORC1 by unknown mechanisms. The Rag complex-dependent activation of mTORC1 signaling has a more important role in regulating lysosomal and mitochondrial homeostasis than does the RHEB axis, which partially explains the upstream signaling inputs required for mTORC1-dependent mitochondrial reprogramming in T cells; however, both the Rag complex and RHEB are essential for regulating glycolytic and mitochondrial oxidative phosphorylation in Treg cells.…”
Section: Induction Of Cellular Metabolismmentioning
confidence: 99%
“…Activation of both complexes Clinical and Experimental Immunology R E V I E W A RT I C L E Series Editors: Sarah Dimeloe and Claudio Mauro promote glucose metabolism, linking mTORC and glycolysis. T regspecific deletion of mTOR reduced their frequency, leading to spontaneous effector T cell activation and inflammation [18]. mTOR activation promotes the differentiation of T helper type 1 (Th1), Th17 [14] and Tfh T cells [13], three effector subsets that are expanded in lupus [15,16].…”
Section: The Yin and Yang Regulation Of Autoimmunity By Mtor And Ampkmentioning
confidence: 99%
“…mTOR activation plays a more complex role in regulatory T cell (T reg ) differentiation and function by preventing the generation of long-lived central T regs , but promoting the generation of effector T regs [17]. T regspecific deletion of mTOR reduced their frequency, leading to spontaneous effector T cell activation and inflammation [18]. Deletion of Lkb1 in T regs , the upstream kinase of AMPK and a well-known sensor of metabolic stress, resulted in dysfunctional T regs and the development of a Th2dominant severe autoimmune phenotype [19,20].…”
Section: The Yin and Yang Regulation Of Autoimmunity By Mtor And Ampkmentioning
confidence: 99%